INSTITUTIONAL ENVIRONMENT OF THE FUNCTIONING OF THE GAS DISTRIBUTION ENTERPRISES OF THE WESTERN REGION (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. This article explores the institutional environment that provides direct action between decision-making by gas distribution entities regarding the operation of special institutions. The institutional environment of gas distribution companies is quite specific and covers external and internal factors. Therefore, we find out the response of gas distribution companies and the variability of the regional environment and the shortcomings of external action. We have proved that the most developed institutional environment covers the presence of the necessary institutions and mutually harmonizes them. This process has a chain reaction to the internal business processes of gas distribution companies, organizational and technical development, as the formation of the international image of the Ukrainian gas transportation system, increasing the quality and reliability of transportation and gas distribution services. Examining the nature of institutions and their impact on enterprise development, they were conditionally divided into active and passive. The purpose of the article. A study of the institutional environment in which gas distribution companies operate in the Western region. Rsults. In summary, it should be made clear that any business entity develops in an appropriate institutional environment, which provides direct decision-making power through the dominance of particular institutions. The development of a particular sector or enterprise as a whole depends on the relevant institutional environment and the qualitative parameters of its functioning. The most developed institutional environment encompasses the need for and coherence between institutions. This process carries out chain activity on internal business processes of gas distribution companies, organizational and technical development, formation of the international image of the Ukrainian gas transport system, increase of quality and reliability of services in transportation and gas distribution. Exploring the nature of institutions and their impact on business development, they should be divided into active and passive. The asset should include well-established and generally accepted rules of conduct. Direct methods reflect economic policy, within the legislative framework. The role of public policy is aimed at realizing the constitutional rights and duties of its citizens. Thus, achieving a mutual effect from the society of sound economic policy is possible provided that the activities of economic entities with the public institutions are coordinated. Public policy is an external factor in influencing the institutional environment, raising the awareness that the quality of the institutional environment will depend on the sectoral management of the activities of the authorities. Therefore, the efficiency of functioning and further development of gas distribution entities is the result of the realization of objective equality between market entities. Objective equilibrium between actors can be achieved by using institutional constraints and incentives for an effective regulatory mechanism. Organizational and resource support for the development of gas distribution and gas transportation companies and making the right decisions by them is significantly complicated by the ramifications of the hierarchical structure of Naftogas of Ukraine and Ukrtransgas. This in turn deforms the interaction between the outer and inner rings of the institutional support of the gas distribution sphere. In order to improve the organizational and managerial structure of the institutional support of the gas distribution sector, progressive technologies and investment attraction should be first of all involved, and the legal system of relations between the subjects of the Ukrainian institutional environment should be streamlined. Conclusions. Hence, it is concluded that the efficiency of the institutions and institutions of the gas distribution system of the region and the state are the most important components in the efficiency of ensuring the level of mesoeconomic and macroeconomic growth. In addition, the presence and efficiency of the necessary institutions shape the appropriate institutional environment, which in turn generates the internal and external effects of the gas distribution sector. Therefore, summarizing we can consider the purpose of the institutional approach of monitoring and stimulation of Ukrainian gas distribution companies, research of the institutions and institutions that regulate it. Therefore, in the future we propose to understand under the institutional environment - purposeful activity and influence of subjects on the functioning of gas distribution companies of the region through the external and internal rings of institutionalization, which synthesize and interconnect legal, political, scientific, economic, social, cultural and other directions directly their improvement and interdependence.
Keywords: institutional environment, gas distribution companies, socio-economic situation of the region, organizational structure of management, competitiveness of enterprises, state policy, infrastructure support